Phenomenological Investigation of Social Media Technological Aspects Against Cyberbullying from the Third Person Perspective of Higher Education Students - Dhewanty, Civica Moehaimin; Priharsari, Diah; Setiawan, Budi Darma (Journal of Information Technology and Computer Science, 2024)
Cyberbullying often occurs among higher education students as they frequently use and easily get access to the internet, especially through social media. However, the awareness of cyberbullying among them is very low. They do not know how to identify cyberbullying and prevent it. This research will discover the characteristics of social media that can help third persons identify and prevent cyberbullying. This research used a qualitative method with a phenomenological approach to study a person’s experience of technology regarding cyberbullying. The data collected in this study were obtained from interviews with higher education students. The data acquired were analyzed using Collaizzi's seven steps descriptive phenomenological analyses. The analysis produced a description of the phenomenon of cyberbullying on social media that have verified by the interviewees. This study found some characteristics of social media to help higher education students identify and prevent cyberbullying and discovers which social media has the most cyberbullying content and the similarities/differences of each social media in helping a third person identify and prevent cyberbullying. And found several technological factors that affect the effort of preventing cyberbullying, such as seeing other people’s activities and personal information on social media, and doing a report or sharing cyberbullying content.